An Innovation Capability Development Process for Firms in Developing Countries: A Theoretical Conceptual Model - Gezahegn Tesfaye; Daniel Kitaw (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Firms in developing nations possess low innovation capabilities due to the absence of an adequate conceptual model that consolidates the innovation capability development (ICD) constructs tailored to their needs. To describe the ICD in these firms, research findings should have consolidated both the technical and financial aspects of innovation. However, they have provided only a little account of information on the ICD process via integrating the technical and financial aspects of innovation. The aim of this research is thus to develop a conceptual model of the ICD process which is highly valuable to firms in developing countries (FDC). Methodologically, this research is based on a broad literature review. Following this, two key findings were obtained. Firstly, three key constructs of ICD, namely knowledge accumulation, knowledge application and fund generation were identified. The first two constructs constitute the technical aspect and the third construct represents the financial aspect of innovation capability. Secondly, using these three key constructs, the research proposed a conceptual model that defines a process of ICD for the FDC. These findings imply that firms’ ICD effort can be better explained by integrating the technical and financial aspects of innovation. As far as our knowledge is concerned, this paper is unique regarding providing a detailed review and discussion regarding the ICD process for FDC. In conclusion, the model can place a great emphasis on the understanding of the key constructs and their relationships to enhance the attitudes and practices of firms to develop their innovation capability.